Homozygous mutations in DZIP1 can induce asthenoteratospermia with severe MMAF. Issue 7 (12th February 2020) - Lv, Mingrong; Liu, Wangjie; Chi, Wangfei; Ni, Xiaoqing; Wang, Jiajia; Cheng, Huiru; Li, Wei-Yu; Yang, Shenmin; Wu, Huan; Zhang, Junqiang; Gao, Yang; Liu, Chunyu; et al.
Abstract : Background: Asthenoteratospermia, one of the most common causes for male infertility, often presents with defective sperm heads and/or flagella. Multiple morphological abnormalities of the sperm flagella (MMAF) is one of the common clinical manifestations of asthenoteratospermia. Variants in several genes including DNAH1, CEP135, CATSPER2 and SUN5 are involved in the genetic pathogenesis of asthenoteratospermia. However, more than half of the asthenoteratospermia cases cannot be explained by the known pathogenic genes. Methods and results: Two asthenoteratospermia-affected men with severe MMAF (absent flagella in >90% spermatozoa) from consanguineous families were subjected to whole-exome sequencing. The first proband had a homozygous missense mutation c.188G>A (p.Arg63Gln) of DZIP1 and the second proband had a homozygous stop-gain mutation c.690T>G (p.Tyr230*). Both of the mutations were neither detected in the human population genome data (1000 Genomes Project, Exome Aggregation Consortium) nor in our own data of a cohort of 875 Han Chinese control populations. DZIP1 encodes a DAZ (a protein deleted in azoospermia) interacting protein, which was associated with centrosomes in mammalian cells. Immunofluorescence staining of the centriolar protein Centrin1 indicated that the spermatozoa of the proband presented with abnormal centrosomes, including no concentrated centriolar dot or more than two centriolar dots. HEK293T cells transfected with two DZIP1 -mutated constructs showed reduced DZIP1 level or truncated DZIP1. The Dzip1 -knockout mice, generated by the CRSIPR-Cas9, revealed consistent phenotypes of severe MMAF. Conclusion: Our study strongly suggests that homozygous DZIP1 mutations can induce asthenoteratospermia with severe MMAF. The deficiency of DZIP1 induces sperm centrioles dysfunction and causes the absence of flagella.